Structural health monitoring of aerospace sandwich structures via strain measurements along zero-strain trajectories. (August 2021) - Bergmayr, Thomas; Winklberger, Markus; Kralovec, Christoph; Schagerl, Martin
Highlights: A SHM method is presented and discussed on the example of an aircraft spoiler. An in-depth numerical study with varying damage sizes is performed. The validation of the numerical results is done by a DIC system and SG measurements. Abstract: This paper investigates a strain-based structural health monitoring (SHM) method for damage detection and localization in composite sandwich structures. As case example, an idealized aircraft spoiler of a large civil aircraft is considered. Critical failure modes of such sandwich structures composed of fiber reinforced polymer (FRP) face layers and a honeycomb core are, e.g., face layer delamination and debonding from the core. The latter challenges today's non-destructive testing methods, and thus, shall be addressed in the present work. The presented research compromises an idealized spoiler model of the real spoiler structure in the scale 1:2. The model is composed of glass fiber reinforce polymer (GFRP) face layers and a honeycomb core. The damage identification is investigated based on static strain measurements along so-called zero-strain trajectories (ZST) at the loaded structure. A zero-strain direction exists for every plane strain state with major strain directions with opposite signs (tensile and compression). Connecting zero-strain direction vectors at various points of a structure yields a ZST. Strains along ZST are most sensitive to changes of the load path due to, e.g., damage. This work investigates the use of strain measurements along ZST for damage detection at the edge of the considered sandwich structure by means of numerical and experimental analysis. A real wind-load condition of a large civil aircraft spoiler is considered as load case. An in-depth numerical and experimental investigation is performed to calculate the ZST for the pristine structure. The experimental validation of the Finite element (FE) model is realized by deformation measurements via a digital image correlation system (DIC). Moreover, strain measurements via strain gauge (SG) rosettes were performed to evaluate the correct calculation of the zero-strain directions. Finally, the application of strain measurements along a ZST for debonding detection and localization is demonstrated and its potential and issues for real online monitoring is discussed.